(untitled) (Բանբեր Երևանի համալսարանի. Բանասիրություն, 2021)
The article introduces the means of expressing imperation and inducement in English as well as the possibilities of their differentiation, similarities and semantic divergences. Some characteristic definitions are also presented, due to which it becomes possible to distinguish imperative and inductive sentences distinctly.